SESSAMO, follow-up of secondary students to assess mental health and obesity: a cohort study - Adriana Goñi-Sarriés; Guillermo Pírez; Nora Yárnoz-Goñi; Francisca Lahortiga-Ramos; Álvaro Iruin; Azucena Díez-Suárez; Iñaki Zorrilla; Leticia Morata-Sampaio; M. Jesús Oliver; Ana González-Pinto; Almudena Sánchez-Villegas (Gaceta Sanitaria)
During last decades, a departure from health-related lifestyles has been observed among adolescents. Evidence reports that healthy lifestyles could be predictors of better mental health status. The aims of the SESSAMO Project are: 1) to assess the association between lifestyles and physical and mental health; 2) to assess how self-concept and stressful life events can modulate these associations; and 3) to establish the role of social determinants in the lifestyle and in adolescents’ health. The SESSAMO Project is a prospective cohort carried out in Spain. Students aged 14-16 years (2nd-4th ESO) and their parents are invited to participate. Baseline data are collected through on-line, validated, self-administered questionnaires through a digital platform. Information on lifestyles, stressful life events and self-concept are collected. Screening of depression, anxiety, eating disorders, suicide risk, psychotic experiences and COVID impact is assessed. Every three years, up to age of 25, participants will be contacted again to update relevant information. Resumen: En las últimas décadas se ha producido un alejamiento de los estilos de vida saludables en adolescentes. Los hábitos saludables pueden predecir una mejor salud mental. El proyecto SESSAMO tiene como objetivos: 1) determinar la asociación entre el estilo de vida y la salud física y mental; 2) determinar cómo el autoconcepto y los acontecimientos vitales estresantes pueden modular dichas asociaciones; y 3) establecer el papel de los determinantes sociales en el estilo de vida y en la salud de los adolescentes. Se trata de un estudio de cohortes prospectivo, dirigido a estudiantes de secundaria de 14-16 años y a sus padres. Los datos basales se recogen con cuestionarios validados y autoadministrados en una plataforma on-line. Se realiza un cribado de depresión, ansiedad, trastornos alimentarios, riesgo de suicidio, experiencias psicóticas e impacto de la COVID-19. Cada 3 años, hasta la edad de 25 años, se les volverá a contactar para actualizar la información relevante.